On the Local Structure of Water Surrounding Inorganic Anions Within Layered Double Hydroxides - Abderrahmane Semmeq; Kanika Anand; Antoine Carof; Adolfo Bastida; Francesca Ingrosso (Molecules)
Understanding the microscopic structure and physical–chemical properties of materials with nanoconfined domains is essential for advancing technologies in catalysis, nanomaterial design, and pharmaceutical applications. Layered double hydroxides (LDHs) are promising candidates for such innovations due to their tunable interlayer environment, which can be precisely controlled by varying the type of intercalated anion and the amount of water present. However, optimizing LDH-based technologies requires detailed insights into the local structure within the interlayer region, where complex interactions occur among anions, water molecules, and the inorganic surfaces. In this work, we present a comprehensive computational study of LDHs intercalating small inorganic anions at varying hydration levels, using atomistic molecular dynamics simulations. Our findings show good agreement with existing experimental and simulation data. We observe that monoatomic ions form either a monolayered or double-layered structures, with water molecules lying flat at low hydration and adopting more disordered configurations near the surfaces at higher hydration. In contrast, polyatomic anions exhibit distinct structural behaviors: nitrates adopt tilted orientations and form double layers at high hydration, similar to perchlorates, while carbonates consistently remain flat. Additionally, water molecules strongly interact with both anions and the surface, whereas anion–surface interactions weaken slightly as hydration increases. These results offer valuable insights into the local structural dynamics of LDHs, paving the way for more efficient design and application of these versatile materials.